Karakterisasi Sifat Agronomi Tanaman Tiga Varietas Cabe Lokal Kabupaten Kepahyang - Asfaruddin Asfaruddin; Farida Aryani (University of Prof. Dr. Hazairin, SH, 2017)
This study aims to find out the character of agronomy in some local chili varieties Kepahyang district. This research was conducted in Tugurejo village, Kabawetan sub – district, Kepahyang district, Bengkulu province. Research fields used include the plateau. The materials used are local scads kepahyang (wulung varieties, Aceh varieties, pendek varieties), manure, organic liquid fertilizer, chemical fertilizers. Tools used are house, handsprayerm sickle, bucket, ajir, mulch, meter, traypoot, ultra violet plastic and stationery. The resparch design used was a Randomized Block Design (RBD) with two factor, the first factor consists of three typus of processed fertilizer, namely liquid organic fertilizer (P1), manure (P2), chemical fertilizer (P3), while the second factor is local varieties, namely wulung (VI). Aceh varieties (V2), pendek varieties (V3). Each treatment was repeated three times. Observed variable were. Plant height, number of harvest crops, fruit diameter, fruit length, total fruit weight, fruit dry weight, flowering age, harvest age. The highest plant height is the manure treatment, significantly different from the treatment of liquid organic fertilizer and chemical fertilizer. The largest a mount of fruit cultivation is wulung varieties treatment, significantly different from the treatment of pendek varieties and aceh varieties. Fruit diameter and fruit length is the best treatment of aceh varieties, significantly different from the treatment of pendek varieties and wulung varieties.